Effect of Ground Vibration to Slope Stability, Case Study Landslide on The Mouth of Railway Tunnel, Gunung Gajah Village, Lahat District - Moamar Aprilian Ghadafi; Muhammad Taufik Toha; Dedi Setiabudidaya (Sriwijaya Journal of Environment, 2017)
Slope stability around railway tunnel in Gunung Gajah Village, Lahat District needs to be analysed due to landslide which occurred on January, 23th 2016. That analysis needs to be done so that the railway transportation system can run safely. The purposes of this research are: to find out the factors that cause slope instability, to find out peak acceleration caused by railway traffic and earthquakes and its effects to the safety factor of slope, and determine stabilization method in order to prevent the occurrence of further landslide. The research activities include surveying, sampling, laboratory testing and analyzing slope stability using pseudo-static approach. Based on research result, the main factors that cause slope instability are morphology, structural geology, and ground vibration caused by earthquakes. Ground vibration are correlated to the slope instability. It shows that the higher of peak acceleration the lower of safety factor of slope. To prevent the occurrence of further landslide around research area, stabilization method should be applied in accordance with the conditions in that area such as building a retaining wall to increase safety factor of slope, building draining channels to reduce run off and performing shotcrete in the wall of landslide in order to avoid weathering.Keywords: ground vibration, slope stability, stabilization method